The role of LMO2 in development and in T cell leukemia after chromosomal translocation or retroviral insertion. - Nam, C; Rabbitts, T (2006)
Chromosomal translocations are primary events in the development of leukemias, representing at least one genetic feature of the putative cancer stem cell. Studies of genes influenced by chromosomal translocations have yielded a vast amount of information about how cancer is initiated and maintained. In particular, acute leukemias have demonstrated that chromosomal translocations often involve transcription regulators that function by interacting with proteins and by controlling cell fate in the aberrant setting of the developing cancer cell. As a quintessential chromosomal translocation gene product, LMO2 has many properties that typify this class of molecule. In addition to its involvement in chromosomal translocations, the LMO2 gene was inadvertently activated in an X-SCID gene therapy trial by retroviral insertion. New molecular therapies targeted directly at the LMO2 protein could have major impact as adjuncts to existing therapies or as therapeutics in their own right. In this review, we outline the current knowledge about LMO2 and some possible routes to develop reagents that might be possible macromolecular drugs in the future.